Internet of Things (IoT) technologies for healthcare : 4th International Conference, HealthyIoT 2017, Angers, France, October 24-25, 2017, Proceedings /: 4th International Conference, HealthyIoT 2017, Angers, France, October 24-25, 2017, Proceedings. (2018) - Unknown
No abstract available